THE EFFECT OF THE UNITED STATES OUT OF PARIS AGREEMENT OF 2015 ON THE NATIONAL SECURITY OF THE UNITED STATES - Hazazi Ridho Subarkah; Yanyan Mochamad Yani; Taufik Hidayat (Sociae Polites, 2019)
This research will discuss climate change, which causes national security threats to several countries. To tackle climate change, the United States ratified the Paris Agreement 2015, but in 2017 the United States left the agreement. The position of the United States is important because it is both an emitter and a cause of climate change. So that climate change influences the national security of the United States. This study was analyzed using the concept of safety and environmental safety. The idea of security used to analyze the threats caused by climate change to the United States national security threats, and the concept of environmental protection is to analyze the ecological crisis as a threat because it is no longer able to sustain human life. This research method with qualitative methods and data collection techniques through a literature study. The results of this study, based on the findings of climate change as a threat to the United States, can have an impact on health, food availability, requests, and coastal areas. It also disrupted military bases and operations in several international and domestic sectors.